Aprendizagem significativa em espaços educativos: o uso dos quelônios como tema facilitador - Almeida, Danielle Portela de (2013)
The learning content of science has always been a subject of fundamental importance in public schools. The scientific content of such manifest in everyday life, it is imperative to purchase these for a better understanding and interaction of reality. The acquisition of knowledge of science is also related to the question of where and how learning occurs. In this context include the Theory of Meaningful Learning developed by Ausubel (1963 ) and its importance in the different educational spaces . Given this reality this research sought to integrate the Theory of Meaningful Learning and educational spaces using the theme of Amazonian turtles, aiming to show the characteristics of these animals and their cultural and economic importance. Thus, the objective of this research was to analyze the possibility of meaningful learning in educational settings using the turtles as tools to facilitate the teaching- learning process. Institutionalized non-formal educational spaces visited by students were: The Laboratory of Amphibians and Reptiles and Science Forest both in National Institute for Research in the Amazon - INPA. This is a qualitative research, we used the techniques of observation, questionnaires, interviews and analysis of the responses of the students resorted to the focus of the content analysis. The subjects of our research were 50 students of the classes 7th of Elementary School Morning of the turn .It was possible to work the Theory of Meaningful Learning in and out of the classroom , in the different educational spaces , developing teaching sequences and exploit the prior knowledge of students . In these spaces the students could find and discover resources and different scenarios not found in the classroom, as well as practical experience in the content covered in class. In this light we understand that it is possible that students learn significantly in different educational spaces using the theme of turtles as a facilitator instrument that the teaching-learning process.